Peningkatan Aktivitas dan Prestasi Belajar Siswa melalui Penerapan Metode Pembelajaran Tutor Sebaya - Siti Juwariyah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to determine the application of learning methods of peer tutor can increase the activity and achievement of students in the competency standard materials National exam graduates in the category of difficult subjects of Science class IX C MTs Negeri 1 Bantul. This research is a class action study conducted in January 2018 to April 2018. Research is conducted in 3 cycles. Cycle I consists of 3 meetings, the II cycle consists of 4 meetings, and the III cycle consists of 2 meetings. The results showed that the application of peer tutor learning methods could increase student learning activities and achievements. Increased student learning activities based on the data of the observation result: category being on cycle I; High category on cycle II, and very high on cycle III. Increased student learning activities based on poll result data: 62.46% at the beginning of study, 62.65% on cycle I, 65.81% in Cycle II, and 78.76% in cycle III. The student learning activity of the results of the entire cycle in the high category. The increase in student achievement is demonstrated by the number of students completed and the classical dictancy. The number of students due to increased from 5 students to the placement test, 2 students in the I cycle, 13 students on the II cycle, and 17 students in the III cycle. The classical dictancy has increased from 17.86% in placement tests, 7.14% on the I cycle, 46.43% in Cycle II, and 60.71% in cycle III.